2022
DOI: 10.3390/ijerph19084466
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Representations of Senior Nursing Students about the Transition to Professional Life during the COVID-19 Pandemic

Abstract: The COVID-19 pandemic caused disruptions in education systems worldwide. The suspension of face-to-face lectures and clinical placements directly impacted nursing students’ learning. This study aimed to identify the perceptions and representations of senior nursing students about the transition to professional life during the COVID-19 pandemic. This descriptive, observational, cross-sectional study used a web-based survey from a convenience sample of 162 senior nursing students, from nine different nursing sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In accordance with this, age was not considered a significant factor affecting the readiness of the nursing students in a Related Learning Experience since most of the students reported having a stressed-associated with performing in clinical practice. (Castro et al, 2022). On the other hand, Elgzar (2019) stated that there was a statistically significant difference between age and sex towards the readiness in Related Learning Experiences through self-directed learning, self-management, self-control, and the willingness to learn.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with this, age was not considered a significant factor affecting the readiness of the nursing students in a Related Learning Experience since most of the students reported having a stressed-associated with performing in clinical practice. (Castro et al, 2022). On the other hand, Elgzar (2019) stated that there was a statistically significant difference between age and sex towards the readiness in Related Learning Experiences through self-directed learning, self-management, self-control, and the willingness to learn.…”
Section: Resultsmentioning
confidence: 99%
“…The gradual development of nursing students' professionalism is a critical aspect of nurturing professional knowledge and clinical skills throughout their academic journey. This process ultimately contributes to the creation of professional nurses who deliver high-quality care and are satisfied with their job in fieldwork (Castro et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The gradual development of nursing students' professionalism is a critical aspect of nurturing professional knowledge and clinical skills throughout their academic journey. This process ultimately contributes to the creation of professional nurses who deliver high‐quality care and are satisfied with their job in fieldwork (Castro et al, 2022). Our primary finding underscores the direct and indirect associations between clinical learning environments, academic satisfaction, clinical competency, and nursing professionalism among nursing students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, a meta-analysis of 27 cross-sectional studies [7] found a high prevalence of depression (34%) among nursing students generally, with younger nursing students (<25 yr.) showing a significantly higher prevalence (41%) than their older counterparts (18%), and Asian nursing students showing the highest prevalence of depression (43%) among geographical groups. Evidence from Portugal related to the transition to professional life of senior nursing students during the pandemic [10] showed that COVID-19 created diverse stressors ranging from "general social risks and fears of the unknown to the more concrete situations related to class interruptions that can postpone the course completion" (p. 5). However, students were equally concerned about non-pandemic issues related to applying their theoretical knowledge in professional practice contexts, particularly in areas such as safe medication administration, communication with multidisciplinary teams, and the fear of making mistakes that could harm patients.…”
Section: Introductionmentioning
confidence: 99%